Critical Review of Trikatu in Ayurvedic classics - BHAVNA SINGH; SARVADEO UPADHYAYA; SUJATA NUNA (Dr. Chinmay Pandya, 2014)
Earthen hemisphere is gifted with varieties of large number of medicinal herbs. Herbs are natural remedies for the disease with higher safety profile and efficacy. India has an ancient heritage of traditional herbal medicine. Ayurvedic literature has a treasure of medicinal herbs in which Trikatu is very important drug. Trikatu is used as solo drug rarely, but it is an essential ingredient of numerous formulations and prescriptions of Ayurvedic medicine. Trikatu is a poly herbal preparation, It consists of three crude drugs namely maricha (Piper nigrum Linn.), Pippali (Piper longum Linn.) and Shunthi (Zingiber officinalis Rosc) in the ratio of (1:1:1; w:w). Trikatu curna is considered as one of the best drugs to treat the condition of Ama(improperly digested absorbed and improperly metabolised food particles including free radicles)  . Trikatu is regarded as the drug of choice in cases of Agnimandya (poor digestion due to faulty digestive process). In Brihattrayi, it is recommended for various diseases due to Agni (digestive fire) vitiation such as Grahaniroga(Malabsorbtion syndrome), Udara roga(major diseases of abdomen surgical and medical like hepatomegaly, spleenomegaly and ascitis ), Arsharoga(piles) etc. The objective of this article is to highlight classification, synonyms, pharmacological actions as described in various diseases, and different formulations of Trikatu in ancient Ayurvedic literature in special reference of Brihattrayi and Nighantus.